"Just how depraved is this town?": An intersectional interrogation of feminist snaps, slut shaming, and sometimes sisterhood in Riverdale's rape culture. Issue 2 (17th February 2022) - Moore, Amber
ABSTRACT: This paper interrogates how rape culture is represented in "Chapter Three: Body Double" of Riverdale through an examination of how it operates through issues of feminism and sisterhood. This case study illustrates the complex ways in which teen television addresses rape culture with increased attention to intersectionality by examining an episode depicting how girls respond to features of rape culture—namely, slut-shaming. Through an intersectional feminist close reading, as well as attending to conceptual frameworks including the "feminist snap" and understandings of sisterhood, I argue that while young women of colour do important work via their feminist snaps, Riverdale 's feminism and sometimes sisterhood are whitewashed, weakening resistance to the local rape culture. This episode represents how Riverdale— to some extent—problematizes understandings of rape culture but ultimately falls short. Furthermore, it gestures towards how popular media such as teen television both clumsily and critically wrangle with storying feminist politics.